Cytotoxic Effect of Brassica oleracea Extract on two Tumor Cell Lines in vitro - Mohammed, Farooq I; Abdullah, Farah T; Abdulfttah, Shaimaa Y (Al-Nahrain Journal of Science, 2013)
This study was conducted to evaluate the cytotoxic effect of B. oleracea oil extract on cancer cell lines and normal cell line in vitro. Two types of tumor cell lines implanted in vitro which were (murine mammary adenocarcinoma, Ahmed-Mohammed-Nahi-2003 (AMN-3) cell line and human Rabdomyosarcama RD cell line). In addition, rat embryo fibroblasts (REF) was used as a normal cell line in this study. Tissue culture plates under sterile condition were treated with different concentrations of B. oleracea extract started from 2.3mg/ml to 300mg/ml for 72 hrs incubation. Results pointed out that B. oleracea extract had a cytotoxic effect depending on the type of cells and the concentration of the extract used for treatment. Results revealed the presence of significant cytotoxic effect on both RD and REF cell lines at concentrations (9.3, 18.7, 37.5 and 75) with percentage of inhibition rate as compared with control and there was not significant effect on AMN3 cell line. Also results showed that growth inhibition was significantly affected and variation in inhibition rate in the same concentration was detected between tumor cell lines and normal cells in this study.